Thermoeconomic analysis and optimization of the small scale power generation and carbon dioxide capture system from liquefied natural gas - Kanbur, Baris Burak (2021)
In the present study, a new small-scale cryogenic CO2 capture and LNG cold utilization system is investigated through the exergetic and thermoeconomic approaches. During the system operation, the condensed water is obtained as the byproduct. The power generation rate and the exergy efficiency reach their maximum points with 27.29 kW and 28.86% at the lowest air temperature and the highest relative humidity, respectively. The minimum levelized product cost is seen as 13.10 $/s at the maximum air temperature and minimum relative humidity values. The component-based assessments show that the heat exchanger, which condenses the water vapor inside, has the highest exergy destruction ratio with the average share of 52.01% while the highest levelized destruction cost is calculated for the combustion chamber with the average value of 1.21 $/s. Also, the impact of levelized component cost is found more significant than the destruction costs. To define the best trade-off point of the proposed system, the multiobjective optimization is performed by using genetic algorithm. The exergy efficiency and the levelized product cost are selected as the objective functions, and the best trade-off points is observed at the ambient temperature of 304.88 K. To better show the advantage of the proposed design in the real environment, a Singapore case study is conducted, and the highest exergetic efficiency and CO2 capture ratio are seen in December with 3.84 and 25.70%, respectively. On the other hand, the levelized product cost presents its minimum value in May with 14.96 $/s whereas the condensed water rate has the highest rate in May as well.